Social Presence as a Moderator of the Effect of Agent Behavior on Emotional Experience in Social Interactions in Virtual Reality - Pfaller, Michael; Kroczek, Leon O. H.; Lange, Bastian; Fülöp, Raymund; Müller, Mathias; Mühlberger, Andreas (Frontiers in Virtual Reality, 2021)
Exposure therapy involves an exposure to feared stimuli and is considered the gold-standard treatment for anxiety disorders. While its application in Virtual Reality (VR) has been very successful for phobic disorders, effects of exposure to virtual social stimuli in Social Anxiety Disorder are heterogeneous. This difference has been linked to demands on realism and presence, particularly social presence, as a pre-requisite in evoking emotional experiences in virtual social interactions. So far, however, the influence of social presence on emotional experience in social interactions with virtual agents remains unknown. We investigated the relationship between realism and social presence and the moderating effect of social presence on the relationship between agent behavior and experienced emotions in virtual social interaction. Healthy participants faced virtual agents showing supportive and dismissive behaviors in two virtual environments (short interactions and oral presentations). At first, participants performed five blocks of short one-on-one interactions with virtual agents (two male and two female agents per block). Second, participants gave five presentations in front of an audience of 16 agents. In each scenario, agent behavior was a within subjects factor, resulting in one block of neutral, two blocks of negative, and two blocks of positive agent behavior. Ratings of agent behavior (valence and realism), experience (valence and arousal), and presence (physical and social) were collected after every block. Moderator effects were investigated using mixed linear models with random intercept, correlations were analyzed via repeated measures correlations. Ratings of valence of agent behaviors showed reliable relationships with experienced valence and less reliable relationships with experienced arousal. These relationships were moderated by social presence in the presentation scenario. Results for the interaction scenario are weaker but potentially promising for experimental studies. Variations in social presence and realism over time were correlated but social presence proved a more reliable moderator. Our findings emphasize the role of social presence for emotional experience in response to specific agent behaviors in virtual social interactions. While these findings should be replicated with experimental designs and in clinical samples, variability in social presence might account for heterogeneity in efficacy of virtual exposure to treat social anxiety disorder.